Water Quality Evaluation of the main Valleys for Agricultural Uses on the left side of Mosul City (Iraqi National Journal of Earth Science (INJES), 2024)
Mg2+>Na+>K+ ), and negative ions(HCO3->SO42->Cl->NO3- ), The classification developed from the Piper water scheme of the studied valleys showed that the water quality in Al-Rashediya Valley is (Ca-Mg-SO4) type , the water quality in both the valley of Al-Khosar and Al-Shor is of the type (Ca-Mg-SO4-Cl). The water quality in Al-Kharrazi Valley is of the type (Alkaline earths exceed alkali metals). While the water quality in Al-Danffilli Valley is of the type (Ca, Mg, HCO3). The classifications of Sodium Adsorption Ratio (SAR), Magnesium Adsorption Ratio (MAR), Sodium Saturation Percentage (SSP), Wilcox scheme, Residual Sodium Carbonate (RSC),]]>
Keywords: IWQI,,; ,،Khosar,,; ,،Shoar,,; ,،Geochemical